Context-aware of homestay recommendation application / Mohd Fakhrulrozi Ramli - Ramli, Mohd Fakhrulrozi (2017)
Homestay is a product and services of tourism that gives an accommodation service which tourist can stay at temporary house. People can determine information about a particular location of homestay and then can detect where a location is placed by using the location detection technologies. The problem comes when the people need to detect the location of homestay accommodation based on their desires which is based on location, area, price, type of accommodation, and anything that can be related to their desired. In this paper, a homestay recommendation application is proposed to help people, especially travelers that want to find the homestay based on their preferences. This application uses the Context-Aware recommendation technique to recommend the homestay and also Global Position System (GPS) to navigate towards the coordinate of homestay. Context-Aware recommendation technique are a particular type of personalized technique which filters information and produces only what is relevant information to use. In the context-aware technique, the context factor which is the coordinate of homestay, type of house, area and price are used to filter the data. The user may state preferences for each of these context factor. Context-A ware technique will filter the each context of the data in the database to recommend the homestay based on the user preferences. Finally, it that the data based on user preferences. In the context of location, it used the GPS technique that can locate the place and also can determine the nearest location of homestay. For the result, the context-aware of homestay recommendation application will recommend the homestay based on the factor of context that the user choose and provide the location of homestay. The evaluation result are conduct by survey to test the functionality of the application that were evaluated by experts.